The Effects of Justice and Burnout on Achievement: An Empirical Investigation of University Students - Uludag, Orhan; Yaratan, Huseyin (Fac Teacher Education, 2013)
The study examined the relationships among justice, burnout, and academic achievement using a sample (N=1,505) of undergraduate university students. The study was conducted at a university in northern part of Cyprus. Hierarchical regression analysis was conducted to test the hypotheses. The results revealed that distributive justice, procedural justice, and interactional justice were associated with burnout. In addition, distributive and interactional justice had a significant positive relationship with academic achievement. Procedural justice had no significant relationship with academic achievement while burnout had a negative association with students' academic achievement. Additionally, burnout was treated as a mediator between justice dimensions and academic achievement. The results of the Sobel test illustrated that burnout partially mediated the effect of distributive and interactional justice on academic achievement. The study provides discussion, limitations and directions for future research.
Keywords: academic achievement; burnout; conservation of resources; equity; higher education